A bibliometric analysis of artificial intelligence in language teaching and learning (1990–2023): evolution, trends and future directions - Ma, Huiling; Ismail, Lilliati; Han, Weijing (Springer, 2024)
The advancement and application of Artificial Intelligence (AI) has introduced innovative changes in language learning and teaching. In particular, the widespread utilization of various chatbots as foreign language learning partners showcases their remarkable potential contribution to the field. Nevertheless, there are currently few studies that encompass extensive and holistic reviews and analyses of the relevant literature during this period. The study employs bibliometric analysis and a systematic review of representative research to present trends, the current status and future directions of AI research in language teaching and learning, providing language educators, policymakers, and research scholars with visually accessible and comprehensive insights. Results indicate that the field is in its early stages of development, growing rapidly with significant research potential. The study identified the most productive and influential sources, institutions, authors and countries and provided a summary for the most representative papers in the research field. Through keyword analysis, the study delineates the evolutionary progression of AI in the domain of language teaching and learning across different time periods, identifies prevailing research trends and proposes future research directions. Results indicate that influential research in this realm predominantly focuses on refining technological solutions and conducting empirical studies on AI applications in language teaching and learning. This highlights significant interest in the effectiveness of AI in language education and its implementation methods. However, research on the application of AI in language education is still in its infancy. Therefore, the study advocates for increased empirical research on AI’s specific applications in language listening, speaking, reading, and writing, as well as the development of more effective pedagogical approaches. Furthermore, the findings reveal a lack of attention given to various concerns and challenges associated with AI utilization in language teaching and learning, such as concerns regarding academic integrity, content authenticity, potential bias, privacy and security issues, and environmental concerns. At present, there is a lack of suitable solutions or regulatory frameworks proposed to address these concerns adequately.